Nutritive value of ground corn fodder (Zea mays) as determine through a digestion trial with steers in cages (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1977)
Three crossbred Jersey steers were used in a digestion trial (in cages), to determine the nutritive value of ground corn fodder (Zea mays). Collection period lasted for seven days (after five days of adaptation to the feed and three days to the cages). Chemical composition of ground corn fodder was as follows: Dry matter (DM) 83.30%; Crude protein (CP) 7.38%; Ether extract (EE) 2.82%; Crude fiber (CF) 19.62%; Nitrogen free extract (NFE) 65.67%. Data for coefficients of digestibility were as follows: DM 57.20%; CP 27.55%)EE 64.57%; CF 42.38%; NFE 66.32%, being the Total Digestible Nutrients equal to 57.99%